(untitled) (Revista científica Olimpia, 2020)
Emotions defined as psychic reactions of great intensity, act at the same time on motor behavior and are accompanied above all by organic phenomena of a neurovegetative nature, so they can influence the degree of effort that must be made and, consequently, on the result of the performances in the trainings and competitions. For this it is important to apply different intervention alternatives to favor the good performance of the athletes. One of these alternatives is the use of floral therapy that as a therapeutic, holistic and reaction method acts on the symptoms that are generated from the emotional state. This work was carried out with the objective of developing floral therapy that allowed adequate emotional control in athletes and therefore greater sports performance. So it was decided to use floral therapy with the benefit that natural remedies are not synthetic chemical active or adverse reactions as the case of psychiatric drugs that can cause affective disorders in behavior and symptoms such as sedation, drowsiness, etc. and the advantage that the benefits are obtained in a short time because it is the most effective system for the recovery of psychophysical harmony to be able to balance or restore energy levels, it is not necessary to use them for a long time. that Floral Therapy contributes to the control of the negative emotional states in the athletes of Artistic Gymnastics and that its application influenced in a 20% in the sports performance reaching from a 4th to a 2nd place.